Renewable energy sources in Latin America and the Caribbean : situation and policy proposals (ECLAC SantiagoCL, 2004)
Examines both the current state and status of renewables in the region. Looks at obstacles, opportunities and key issues for the penetration of renewable sources. Deals with public policy-making key issues, proposals and a strategy for renewable resources of energy.
Bibliography: p. 129-133